2016
DOI: 10.17221/226/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Pendimethalin degradation in soil and its interaction with soil microorganisms

Abstract: Pendimethalin [N-(1-ethylpropyl)-3,4-dimethyl-2, 6-dinitrobenzenamine] is a herbicide used worldwide to control most annual grasses and common weeds in cereals, fruit, and vegetables. Its degradation in Haplic Chernozem under controlled greenhouse conditions was studied in this paper. The effect of recommended and doubled pendimethalin doses, as well as the effect of the biopreparate EM-EKO ProBio Plus on pendimethalin degradation in soil and on soil microorganisms was investigated. Pendimethalin half-life ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Strange-Hansen et al (2004) stated that glyphosate degradation in the soil environment is a cometabolic process and the rate of decomposition would depend on the general activity of microbial populations, the type of soil and environmental conditions. Kočárek et al (2016) in a study on pendimethalin degradation in a haplastic chernosol, under controlled conditions, did not observe any effect of pendimethalin on the quantity or activity of soil microorganisms. But it was observed that the fungi Aspergillus fumigatus and Penicillium citrinum used this herbicide as a carbon source in the present research.…”
Section: Resultsmentioning
confidence: 86%
“…Strange-Hansen et al (2004) stated that glyphosate degradation in the soil environment is a cometabolic process and the rate of decomposition would depend on the general activity of microbial populations, the type of soil and environmental conditions. Kočárek et al (2016) in a study on pendimethalin degradation in a haplastic chernosol, under controlled conditions, did not observe any effect of pendimethalin on the quantity or activity of soil microorganisms. But it was observed that the fungi Aspergillus fumigatus and Penicillium citrinum used this herbicide as a carbon source in the present research.…”
Section: Resultsmentioning
confidence: 86%
“…On the contrary, an insignificant effect of doubled application rate on herbicides dissipation was documented by Tsiropoulos and Miliadis (1998), Kewat et al (2001) and Jursík et al (2016). Finally, Kočárek et al (2016) observed a shorter half-life for pendimethalin when the pendimethalin application rate was doubled. Vertical soil transport of herbicides.…”
Section: Sunflower Injurymentioning
confidence: 95%
“…The modi ed method by Kočárek et al (2016) was used to determine the residual concentration of herbicides in soil solution (µg cm − 3 ) using the HPLC (Dionex; USA) technique. The rate of degradation and half-life (DT 50 ) of herbicides were calculated using the following equation:…”
Section: Degradation Experimentsmentioning
confidence: 99%